Bermain Pasir Buatan dan Koordinasi Mata-Tangan Anak Usia Dini di Gorontalo - Ardini, Pupung Puspa; Edila Abdul, Velly Sena; Utoyo, Setiyo (Universitas Nusantara PGRI Kediri, 2023)
The aim of this research is to determine the information obtained from playing with an artificial sand environment on the eye-hand coordination abilities of young children. This study is a quantitative research using an experimental method and a one-group pre-test-post-test design. The respondents consisted of 22 children aged 5 to 6 years. The results of the research indicate a significant difference in the average eye-hand coordination abilities of children before and after the treatment, as evidenced by the scores obtained in the pre- and post-tests, which were 40.9% and 68.1% respectively. Although the t-test calculation yields a significant value of < 0.05, specifically 0.00, rejecting the null hypothesis (Ho), these results indicate a significant influence before and after the treatment. It is necessary to design and implement regular play activities according to the themed sand play in the classroom as a medium to stimulate eye-hand coordination. Additionally, it is important to disseminate this information to groups of teachers in the vicinity of the research location.